Mites (Arachnida: Acari) associated with Calliphoridae flies (Diptera: Oestroidea) at three localities in Panama - MIRANDA, ROBERTO; BERMÚDEZ, SERGIO (Revista Colombiana de Entomología, 2008)
The discovery of 54 mites adhered to 23 individuals of Calliphoridae flies, in three wooded sites in Panama, is reported. The mites corresponded to adults of the species Ancistrocheles bregetovae and Macrocheles spp. (Macrochelidae), larvae of Leptus spp. (Erythraeidae) and deutonymphs of Myanoetus sp. (Histiostomatidae). The first report is made of the association between parasitic Leptus spp. with Calliphoridae flies, and in the same way information is broadened on the hosts of A. bregetovae.